Long-cycled Li2ZnTi3O8/TiO2 composite anode material synthesized via a one-pot co-precipitation method for lithium ion batteries. (5th January 2017) - Li, Hua; Li, Zhoufu; Cui, Yanhui; Ma, Chenxiang; Tang, Zhiyuan
Abstract : Li2 ZnTi3 O8 and Li2 ZnTi3 O8 /TiO2 anode materials were synthesized via a co-precipitation method and displayed excellent electrochemical performances. Abstract : Li2 ZnTi3 O8 /TiO2 composite anode materials were synthesized by using a one-pot co-precipitation method for the first time. Texture characteristic and electrochemical measurements were taken of this composite and of pure as-prepared Li2 ZnTi3 O8 to investigate their structures, morphologies and electrochemical properties. The Li2 ZnTi3 O8 /TiO2 composite anode material showed a better cycle performance and a higher rate performance than did the pure Li2 ZnTi3 O8 . At current densities of 1000 mA g −1, 2000 mA g −1 and 3000 mA g −1, the dual-phased Li2 ZnTi3 O8 /TiO2 composite yielded discharge capacities, respectively, of 211.1 mA h g −1, 199.8 mA h g −1 and 180.8 mA h g −1 at the first cycle, and 150.6 mA h g −1, 137.2 mA h g −1 and 108.2 mA h g −1, respectively, after 1000 cycles. The high specific capacity together with outstanding rate and cycle performance of the Li2 ZnTi3 O8 /TiO2 composite suggest it to be a promising anode material for lithium ion batteries.